Using micronutrients effectively for management of sugarcane chlorosis - Chandrashekhar, C P; Chittapur, B M; Kulkarni, Venkatesh; Biradar, D P (Indian Farming, 2016)
Sugarcane chlorosis is widespread these days due to deficiency of iron and zinc, and consequently cane productivity is coming down. Studies on farmers’ fields using soil application of 25 kg/ha each of FeSO4 and foliar application of 0.5% FeSO4 and ZnSO4 two to three times based on intensity of chlorosis helped crop recovery and produced higher cane yields in the Ghataprabha left Bank Canal command of Karnataka. Hence sugarcane growers experiencing crop chlorosis problem may use these recommendations.